FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Peridode 2013-2015) - Nawangsetri Pramusita, 13.05.52.0038; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
This study aims to examine and provide empirical evidence of the effect of liquidity, leverage, profitability, independent commisioner and firm size against the aggressiveness of the tax on manufacturing companies listed on the Indonesia Stock Exchange from 2013 to 2015. Samples were companies listed on the Indonesia Stock Exchange 2013-2015 by using purposive sampling. The analytical method used in this research is the method of multiple linear regression analysis. The results of this study indicate that liquidity significant negative effect on the aggressiveness of the taxes while leverage, profitability, Â independent commisioner, and firm sizeâs significant negative effect on the aggressiveness of tax.Keywords:Â Liquidity, Leverage, Profitability, Independent Commissioner, and Firm Size, Tax Aggressive